Periodic limb movements in patients with suspected obstructive sleep apnea without comorbid conditions - Seifen, Christopher; Herrmann, Moritz; Pordzik, Johannes; Matthias, Christoph; Gouveris, Haralampos (Frontiers in Medicine, 2024)
Background: Periodic limb movement disorder (PLMD) and obstructive sleep apnea (OSA) are overlapping clinical syndromes with common risk factors. However, current literature has failed to establish a clear pathophysiological link between them. Thus, little is known about periodic limb movements (PLM) in otherwise healthy patients with suspected OSA. Methods: We performed a retrospective analysis of 112 patients (age: 44.5 ± 12.0 years, 14.3% female) with suspected OSA who underwent full night polysomnography for the first time. Patients with chronic diseases of any kind, recent infections, malignancies, or daily or regular use of any type of medication were excluded. Group comparisons were made based on the severity of OSA (using the apnea hypopnea index, AHI) or the periodic limb movement index (PLMI). Results: Both, PLMI and the total number of periodic limb movements during sleep (PLMS), showed a significant increase in patients with severe OSA. In addition, AHI and apnea index (AI) were significantly higher in patients with PLMI > 15/h, with a similar trend for hypopnea index (HI) (p < 0.001, p < 0.001, and p > 0.05, respectively). PLMI was significantly positive correlated with AHI, AI, and HI (r = 0.392, p < 0.001; r = 0.361, p < 0.001; and r = 0.212, p < 0.05, respectively). Patients with PLMI > 15/h were significantly older (p < 0.001). There was no significant association between body mass index (BMI) and PLMI > 15/h.We found a significant association between the severity of OSA and PLM in our study population with suspected OSA but without other comorbidities. PLMI and PLMS were significantly increased in patients with severe OSA. Future prospective studies with larger collectives should verify the presented results and should include mechanistic aspects in their evaluation.